Gendered Narratives in Climate Justice and the Role of Women’s Leadership in Environmental Movements - Damar, Arjuna; Fahri, Fahri; Rizki, Bima (Journal Social Humanity Perspective, 2025)
It is a qualitative inquiry that examines how the central role of female leadership in shaping gendered discourses in climate justice movements is done, and how their agency and practical actions reshape environmental activism and social justice. Drawing upon extensive in-depth interviews with women leaders in a range of environmental movements, the analysis shows that they understand climate justice in terms of an intersectional approach of ecological stewardship in relation to the well-being of communities, cultural identity, and gender equality. Their stories highlight the relationship between the environmental degradation and social inequality, thus highlighting the need to have a combined and inclusive leadership to achieve sustainable solutions. Despite their irreplaceable roles, women still face institutional barriers including patriarchal marginalization, economic marginalization and restricted access to decision making spaces. Using the thematic analysis, this work determines how women transform these limitations into opportunities to take innovative and community-based climate action. Its results dispute existing technocratic, male-dominated leadership paradigms and suggests a more comprehensive approach to environmental governance with empathy, collaboration, and indigenous local expertise as its priority. This research has implications on management and policymaking, which propose gender-responsive policies that would institutionalize the leadership of women in climate governance. In the end, the work also claims that climate justice cannot be achieved without gender justice because the female leadership is not only redressing but transformational to the world environmental organizations.